Night shift work and breast cancer risk: what do the meta-analyses tell us? - Manisha Pahwa; France Labrèche; Paul A Demers (Nordic Association of Occupational Safety and Health (NOROSH), 2018)
OBJECTIVES: This paper aims to compare results, assess the quality, and discuss the implications of recently published meta-analyses of night shift work and breast cancer risk. METHODS: A comprehensive search was conducted for meta-analyses published from 2007-2017 that included at least one pooled effect size (ES) for breast cancer associated with any night shift work exposure metric and were accompanied by a systematic literature review. Pooled ES from each meta-analysis were ascertained with a focus on ever/never exposure associations. Assessments of heterogeneity and publication bias were also extracted. The AMSTAR 2 checklist was used to evaluate quality. RESULTS: Seven meta-analyses, published from 2013-2016, collectively included 30 cohort and case-control studies spanning 1996-2016. Five meta-analyses reported pooled ES for ever/never night shift work exposure; these ranged from 0.99 [95% confidence interval (CI) 0.95-1.03, N=10 cohort studies) to 1.40 (95% CI 1.13-1.73, N=9 high quality studies). Estimates for duration, frequency, and cumulative night shift work exposure were scant and mostly not statistically significant. Meta-analyses of cohort, Asian, and more fully-adjusted studies generally resulted in lower pooled ES than case-control, European, American, or minimally-adjusted studies. Most reported statistically significant between-study heterogeneity. Publication bias was not evident in any of the meta-analyses. Only one meta-analysis was strong in critical quality domains. CONCLUSIONS: Fairly consistent elevated pooled ES were found for ever/never night shift work and breast cancer risk, but results for other shift work exposure metrics were inconclusive. Future evaluations of shift work should incorporate high quality meta-analyses that better appraise individual study quality.